Mistrust of the City at Night: Networked Connectivity and Embodied Perceptions of Risk and Safety. Issue 107 (2nd January 2021) - Hardley, Jess; Richardson, Ingrid
ABSTRACT: This article explores the embodied experience of smartphone users in urban darkness, and considers how the geo-locative and network functionality of mobile media impacts upon the perception of safety and risk at night. City spaces at nighttime are often perceived as less safe, and the habitual trust we place in familiar strangers during the day can becomes imbued with caution, suspicion and fear. Women in particular are typically advised to reduce nighttime risk by remaining in well-lit, more populated areas, not travelling alone, and keeping mobile phones handy. Indeed, in contemporary popular culture, media coverage increasingly links heightened physical safety with the use of geolocative mobile media – this is evident in the reporting of the sexual assaults and murders of Jill Meagher, Eurydice Dixon, and Aiia Maasarwe in Australia, and Mollie Tibbetts in the United States. This article draws on original ethnographic data collected in Perth and Melbourne (Australia) from 2016 to 2020 to examine how mobile devices as both communicative and location-aware interfaces are used to provide women with a perceived or 'felt' sense of bodily safety and security, and the potential implications this has on users' pedestrian traversal of the urban dark.